Il teatro secondo Badiou: L’evento del pensiero tra eterno testuale e istante scenico - Chillemi, Francesco (Mimesis Journal, 2017)
This article reconstructs the key passages of the theory of theatre elaborated by French philosopher Alain Badiou. A particular attention is dedicated to four texts: Rapsody for the theatre (the heftiest of the eight essays included in the collection), in which it is enunciated the veritative power of the theatre – onto which scene the encounter between the textual eternity and the scenic instant gives life to events of thought; the programmatic essays Ten thesis on the theatre and Antithesis of the theatre, which explicitly renders the terms of the crucial relationship between truth and art. The sheer originality of Badiou’s heterodox re exion on theatre is the result of a distance from the principles of the theatre of direction and from the strongholds of the «postdramatic theatre» (Hans-Thies Lehmann, 1999). On the one hand, there is a rejection of any theory which makes of the theatrical praxis the enactment of ‘external truths’, that the representation was supposed to make visible. On the other hand, the anti-textual and performative position of the experimental avant-gardes is declined: the protagonists of the theatre are the playwright, the director (the two figures properly artistic) and the spectators («the holders of the theatre-idea»). The true theatre is therefore the «theatre of ideas», of which the actors are nothing but the «pure presence», the mediation, the «ethical mean».